The Impact of HAINC-Integrated NotebookLM AI Feedback on EFL Students’ Writing Performance at IAIN Parepare - Winny Junianty Imradiyah; Nurul Hasanah; Zulfah Fakhruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigated the impact of HAINC-Integrated NotebookLM AI feedback on EFL students’ writing performance at IAIN Parepare. The study employed a quantitative pre-experimental design using a one-group pre-test and post-test method combined with a Technology Acceptance Model (TAM) questionnaire. The participants consisted of 23 students from the English Education Study Program selected through purposive sampling. The instruments used in this study were a writing test and a TAM-based questionnaire. The writing assessment focused on four components: content and ideas, organization and structure, language and style, and grammar and punctuation. The treatment was conducted using NotebookLM integrated with the Human-AI Interactive Negotiation Competence (HAINC) protocol, which applied Socratic interaction, progressive prompting, and the “Three-Try Rule” to encourage active learner engagement during revision activities. The collected data were analyzed using descriptive statistics and a paired sample t-test. The findings revealed a significant improvement in students’ writing performance after the implementation of the AI feedback system, as indicated by the significance value of 0.003 (<0.05). Furthermore, the TAM questionnaire results showed that students demonstrated a high level of technology acceptance toward NotebookLM AI feedback in terms of perceived usefulness, perceived ease of use, attitude toward using AI, and behavioral intention to use the technology. The study concludes that HAINC-Integrated NotebookLM AI feedback effectively improves students’ writing performance and positively supports AI-assisted learning in EFL writing instruction